Design of Compact Metal-Mountable Uhf RFID Tag Antenna - Tan, Jiun Ian (2021)
A new type of UHF RFID tag antenna, which consists of four elementary shorted patches, a feeding loop, and a ground plane, is proposed for designing a compact metal-mountable UHF RFID tag antenna. The feeding loop in Layer 2 is incorporated for exciting the shorted patches in Layer 1 and Layer 3 simultaneously through inductive coupling. The patches in Layer 1 and Layer 3 are tactfully combined with the narrow stubs before shorted to the ground plane through a shorting via. The narrow stubs are to provide additional inductance for this antenna to conjugate match with the chip impedance. As a result, a high power transmission coefficient of 93.5% is achieved. Apart from improving the matching level, the stubs are also very useful for tuning the resonant frequency to the desired UHF band. The tag antenna has a miniature size of 30 mm × 30 mm × 3.18 mm (0.0914 λ × 0.0914 λ × 0.0096 λ). Despite being electrically small and low in profile, the proposed antenna can produce a stable omnidirectional radiation pattern when being mounted to a metal plate of 200 mm × 200 mm × 10 mm during the measurement process with the detection range up to 6.25 m. The tag has a stable resonant frequency of 914 MHz and it is not affected much by changes in the backing metal.